Metode Pembelajaran Guru Aqidah Akhlak : (Penelitian di Kelas XI IPS 2 MA Ar Rosyidiyah Bandung) - Farida, Nur Aini; Nurhasan, Nurhasan (Magister PAI Universitas Singaperbangsa Karawang, 2023)
This study intends to find out the actual nature of the Aqidah Akhlak learning technique, find the issues associated with applying learning methods in Aqidah Akhlak subjects, and find solutions to these issues. An observation-based qualitative method of data collecting was employed in the development of this study. The results of the analysis show that the reality of the teacher uses the learning method from the learning method carried out by Dra. Wiwi Marwiyah, M.Pd.I in the subject of Aqidah Akhlak with hypocrisy and ghadab material is to use lecture, question and answer and discussion methods. In the learning process, the teacher comes in and starts it in a timely, informative, and interactive manner. As for the problems with using the learning method, there are still students chatting when the teacher explains using the lecture method, and the teacher has not succeeded in getting students to appear in front of them to re-present the material that has been delivered. Thus, hypocritical and ghadab material is not compatible with the lecture method, so CTL (contextual teaching and learning) and PBL (problem-based learning) methods must be used.